Development and evaluation of a duplex TaqMan qPCR assay for detection and quantification of Trypanosoma cruzi infection in domestic and sylvatic reservoir hosts - Wehrendt, Diana Patricia (2019)
Background: A question of epidemiological relevance in Chagas disease studies is to understand Trypanosoma cruzi transmission cycles and trace the origins of (re)emerging cases in areas under vector or disease surveillance. Conventional parasitological methods lack sensitivity whereas molecular approaches can fill in this gap, provided that an adequate sample can be collected and processed and a nucleic acid amplification method can be developed and standardized. We developed a duplex qPCR assay for accurate detection and quantification of T. cruzi satellite DNA (satDNA) sequence in samples from domestic and sylvatic mammalian reservoirs. The method incorporates amplification of the gene encoding for the interphotoreceptor retinoid-binding protein (IRBP), highly conserved among mammalian species, as endogenous internal amplification control (eIAC), allowing distinction of false negative PCR findings due to inadequate sample conditions, DNA degradation and/or PCR interfering substances. Results: The novel TaqMan probe and corresponding primers employed in this study improved the analytical sensitivity of the assay to 0.01 par.eq/ml, greater than that attained by previous assays for Tc I and Tc IV strains. The assay was tested in 152 specimens, 35 from 15 different wild reservoir species and 117 from 7 domestic reservoir species, captured in endemic regions of Argentina, Colombia and Mexico and thus potentially infected with different parasite discrete typing units. The eIACs amplified in all samples from domestic reservoirs from Argentina and Mexico, such as Canis familiaris, Felis catus, Sus scrofa, Ovis aries, Equus caballus, Bos taurus and Capra hircus with quantification cycles (Cq´s) between 23 and 25. Additionally, the eIACs amplified from samples obtained from wild mammals, such as small rodents Akodon toba, Galea leucoblephara, Rattus rattus, the opossums Didelphis virginiana, D. marsupialis and Marmosa murina, the bats Tadarida brasiliensis, Promops nasutus and Desmodus rotundus, as well as in Conepatus chinga, Lagostomus maximus, Leopardus geoffroyi, Lepus europaeus, Mazama gouazoubira and Lycalopex gymnocercus, rendering Cq´s between 24 and 33. Conclusions: This duplex qPCR assay provides an accurate laboratory tool for screening and quantification of T. cruzi infection in a vast repertoire of domestic and wild mammalian reservoir species, contributing to improve molecular epidemiology studies of T. cruzi transmission cycles.